Semi‐Mechanism‐Based Pharmacokinetic/Pharmacodynamic Model for the Combination Use of Dexamethasone and Gemcitabine in Breast Cancer. Issue 12 (7th September 2015) - Yuan, Yin; Zhou, Xuan; Ren, Yupeng; Zhou, Shupei; Wang, Lijie; Ji, Shuangmin; Hua, Ming; Li, Liang; Lu, Wei; Zhou, Tianyan
Abstract : Our study aimed at the investigation of in vivo anticancer effect of the combination use of dexamethasone (DEX) and gemcitabine (GM) as well as the development of pharmacokinetic/pharmacodynamic (PK/PD) models in MCF‐7 xenograft model. Further, simulations were conducted to optimize doses and administration schedules. The inhibitory effect of different doses and administration schedules were investigated in MCF‐7 xenograft model. Semi‐mechanism‐based PK/PD models were established based on the preclinical data to characterize the relationship between plasma concentration and the time course of the drug response quantitatively. The PK/PD models were further applied to predict and optimize doses and administration schedules, which would lead to tumor stasis by the end of the treatment. Synergistic effect was observed in the PD study in vivo and further confirmed by the estimated combination index ψ obtained from PK/PD models. The optimum dose regimen was selected as DEX 2 mg/kg, qd and GM 10 mg/kg, q2d based on the simulation results. In summary, the PD interaction between DEX and GM was demonstrated as synergism by both experimental results and modeling approach. Dosage regimens were optimized as predicted by modeling and simulations, which would provide reference for preclinical study and translational research as well. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4399–4408, 2015